Savoir-faire locaux et auto-construction dans la toundra. Une lecture des cabanes du fjord de Salluit (Note de recherche) - Demeule, Pierre-Olivier (Études Inuit Studies, 2020)
Considered informal from a western perspective, Nunavik’s cabins mark the evolution of a way of life inherited from Inuit tradition and reveal a know-how rich in solutions to the communities’ housing crisis. Composed of objects and materials that are mostly recycled, diverted or acquired randomly, these cabins are ingeniously deployed on the tundra in a way that is as admirable as the resilience of their builders. In terms of architecture, two questions stand out: how are these cabins built and how could a better understanding of their composition enrich a shared vision of northern architecture? The meeting with local self-builders and the in situ observations of cabins along the Salluit Fjord (Nunavik) in August 2018 suggest a tangible response addressing both the conceptual and constructive processes of the cabins. Formulated as a reflexive feedback on these encounters and observations, this article proposes a reading of the tundra cabins through a “graphic deconstruction” of their components. By studying each of the elements layer by layer, this process opens the perspectives of a detailed understanding of the making, the occupation and the transformation of the cabins. Finally, the study proposes a categorization of the various types of cabins found in the Salluit fjord. By their respective characteristics, these types reflect the variations of a relationship to the land that is still key to the culture of Nunavimmiut. Considérées comme informelles du point de vue occidental, les cabanes du Nunavik marquent l’évolution d’un mode de vie hérité de la tradition inuit et révèlent un savoir-faire riche de solutions face à la crise du logement des communautés. Composées d’objets et de matériaux pour la plupart recyclés, détournés ou acquis aléatoirement, ces cabanes se déploient ingénieusement au coeur de la toundra d’une manière aussi admirable qu’est la résilience de leurs bâtisseurs. À l’égard de l’architecture, deux questions se posent : comment sont construites ces cabanes et comment une meilleure ...